2015
DOI: 10.1007/s12011-015-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boric Acid Supplementation on the Expression of BDNF in African Ostrich Chick Brain

Abstract: The degree of brain development can be expressed by the levels of brain brain-derived neurotrophic factor (BDNF). BDNF plays an irreplaceable role in the process of neuronal development, protection, and restoration. The aim of the present study was to evaluate the effects of boric acid supplementation in water on the ostrich chick neuronal development. One-day-old healthy animals were supplemented with boron in drinking water at various concentrations, and the potential effects of boric acid on brain developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Our results are similar to the previous studies which show that ethanol can trigger apoptosis (Cohen et al 2009;Sogut et al 2017). Tang et al also demonstrated that proper doses of boric acid (160 mg/L most) prevents apoptosis and brain development damage in ostrich chick brains (Tang et al 2016).…”
Section: R a F Tsupporting
confidence: 92%
“…Our results are similar to the previous studies which show that ethanol can trigger apoptosis (Cohen et al 2009;Sogut et al 2017). Tang et al also demonstrated that proper doses of boric acid (160 mg/L most) prevents apoptosis and brain development damage in ostrich chick brains (Tang et al 2016).…”
Section: R a F Tsupporting
confidence: 92%
“…50 The other reason might be the effect of BA on the caspase-3 gene expression, because caspase-3 has a critical role in programmed cell death (apoptosis). 51 It is also reported that a low concentration of borate/boric acid solution leads to necrosis rather than to apoptosis. 45 The results of apoptosis/necrosis assay on HUVECs are shown in Figure 9c,d.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…A study conducted on rats by Ince et al demonstrated the antioxidant properties of BA and its effectiveness against LP (22). Another study proposed that BA taken at low doses regularly promotes brain development by reducing apoptosis (40).…”
Section: Zeki Serdar Ataizimentioning
confidence: 99%